Asking a question

Ad

This is best written as two separate equations:

8x+3y = -23 and 34x+ 5y = -23

Solving the first one for x:

8x = -23-3y

x = -23/8 - 3/8y

Substituting this value for x into the second equation:

34(-23/8 - 3/8y) + 5y = -23

-97.75 - (34)(.375)y + 5y = -23

-97.75 - 12.75y + 5y = -23

-97.75 -7.75y = -23

-7.75y = 97.75-23=74.75

**y **= -74.75/7.75 =** -9.645161**

Substitution back into the equation for x:

x = -23/8 - 3/8(-9.645161)

x = -2.875 + 3.616935

**x** **=.741935**

Posted on Dec 13, 2014

Ad

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of.(from cars to computers, handyman, and even drones)

click here to download the app (for users in the US for now) and get all the help you need.

Goodluck!

Posted on Jan 02, 2017

Ad

1) 2x + 5y = 7

2) 3x + 6y = 3

I'm going to use the method of elimination to solve for x and y.

Multiply 1) by 3 and 2) by 2 to allow the x's to be eliminated.

1) 6x + 15y = 21

2) 6x + 12y = 6

Now subtract line 2 from line 1.

0x + 3y = 15

---- ----

3 3 divide both sides by 3 to get y by itself.

y =5.

Substitute into 1) to calculate x.

2x + 5(5) = 7

2x + 25 = 7

2x + 25 -25 = 7 - 25

2x = -18

---- ----- divide both sides by 2 to get x by itself

2 2

x = -9

Check by plugging in answer into the other equation, in this case 2)

3 (-9) + 6(5) = 3

-27 + 30 = 3

3 = 3

We did it correctly and checked to prove that we did it right.

Good luck.

Paul

2) 3x + 6y = 3

I'm going to use the method of elimination to solve for x and y.

Multiply 1) by 3 and 2) by 2 to allow the x's to be eliminated.

1) 6x + 15y = 21

2) 6x + 12y = 6

Now subtract line 2 from line 1.

0x + 3y = 15

---- ----

3 3 divide both sides by 3 to get y by itself.

y =5.

Substitute into 1) to calculate x.

2x + 5(5) = 7

2x + 25 = 7

2x + 25 -25 = 7 - 25

2x = -18

---- ----- divide both sides by 2 to get x by itself

2 2

x = -9

Check by plugging in answer into the other equation, in this case 2)

3 (-9) + 6(5) = 3

-27 + 30 = 3

3 = 3

We did it correctly and checked to prove that we did it right.

Good luck.

Paul

Mar 12, 2015 | Office Equipment & Supplies

There are an infinite number of solutions. The equation is that of a straight line, which has an infinite number of points. At any point on the line there is a unique value of x.

Nov 06, 2014 | Office Equipment & Supplies

To find the solution, first find the value of y for each equation.

Then substitue one equation into the other so that you only the x variable left.

Then just solve for x.

Once you have a value for x, then you can easily solve for y.

So for the first equation:

3y - 6x = -3

3y = 6x - 3

**y = 2x - 1**

Now for the second equation:

2y + 8x = 10

2y = -8x + 10

**y = -4x + 5**

Since both equations equal y, they also equal each other, therefore:

2x - 1 = -4x + 5

Now just solve for x:

2x + 4x = 5 + 1

6x = 6

**x=1**

Now substitute x=1 into either original equation:

y = 2x - 1

y = 2 (1) - 1

y = 2 - 1

**y = 1**

Therefore the solution is x=1 and y=1

Good luck, I hope that helps.

Joe.

Then substitue one equation into the other so that you only the x variable left.

Then just solve for x.

Once you have a value for x, then you can easily solve for y.

So for the first equation:

3y - 6x = -3

3y = 6x - 3

Now for the second equation:

2y + 8x = 10

2y = -8x + 10

2x - 1 = -4x + 5

Now just solve for x:

2x + 4x = 5 + 1

6x = 6

y = 2x - 1

y = 2 (1) - 1

y = 2 - 1

Good luck, I hope that helps.

Joe.

Nov 09, 2011 | Texas Instruments TI-84 Plus Silver...

Todd is 4 years old.

Let Tom's age = X

Let Todd's age = Y

From the given facts:

X = 5Y

and

X + 7 + 6 = 3 ( Y + 7 )

X+13 = 3Y + 21

X = 3Y + 8

So if:

X=5Y

and

X=3Y+8

Then:

5Y=3Y+8

2Y=8

Y=4

I hope that helps.

Joe.

Let Tom's age = X

Let Todd's age = Y

From the given facts:

X = 5Y

and

X + 7 + 6 = 3 ( Y + 7 )

X+13 = 3Y + 21

X = 3Y + 8

So if:

X=5Y

and

X=3Y+8

Then:

5Y=3Y+8

2Y=8

Y=4

I hope that helps.

Joe.

Sep 14, 2011 | Office Equipment & Supplies

Select the EQN computational mode 5:EQN

For system of linear equations in 3 unknowns select 2: in the screen below.

Arrange the variables in your equations in the same order (x first, y second, and z third).

The coefficients to enter in the editor are the factors of the variables: In your case a_1=10, b_1=-3, c_1=10, d_1=5, a_2=8, b_2=-2, c_2=9, d_2=3; a_3=8, b_3=1, c_3=-10, d_3=7.

To enter d_1, d_2, and d_3 you will have to scroll to the right to reach the cells where they should go.

Once finished entering the coefficients, press EXE to get the solutions. You may have to use the arrow Down to display the y- and z-solutions.

I verified that the matrix is non-singular and the system has a solution. In fraction form

x=27/53, y=-1 and 22/53; finally z=-23/53

For system of linear equations in 3 unknowns select 2: in the screen below.

Arrange the variables in your equations in the same order (x first, y second, and z third).

The coefficients to enter in the editor are the factors of the variables: In your case a_1=10, b_1=-3, c_1=10, d_1=5, a_2=8, b_2=-2, c_2=9, d_2=3; a_3=8, b_3=1, c_3=-10, d_3=7.

To enter d_1, d_2, and d_3 you will have to scroll to the right to reach the cells where they should go.

Once finished entering the coefficients, press EXE to get the solutions. You may have to use the arrow Down to display the y- and z-solutions.

I verified that the matrix is non-singular and the system has a solution. In fraction form

x=27/53, y=-1 and 22/53; finally z=-23/53

Jun 29, 2011 | Casio FX-115ES Scientific Calculator

Is this a maths school problem?

You need to use algebra -

2x + 5y = 232 (heena has a number of 2 and 5 coins in her purse which add up to 232)

x + y = 80 (heena has x number of 2 and y number of 5 coins which tally to 80)

therefore, x = 80 - y

so going back to first equation, 2(80 - y) + 5y = 232

160 - 2y + 5y = 232

3y = 72

y = 24

and going back to x, x = 80 - y

x = 80 - 24

x = 56

so heena has 56 rs 2, and 24 rs 5. So the answer is 24.

You need to use algebra -

2x + 5y = 232 (heena has a number of 2 and 5 coins in her purse which add up to 232)

x + y = 80 (heena has x number of 2 and y number of 5 coins which tally to 80)

therefore, x = 80 - y

so going back to first equation, 2(80 - y) + 5y = 232

160 - 2y + 5y = 232

3y = 72

y = 24

and going back to x, x = 80 - y

x = 80 - 24

x = 56

so heena has 56 rs 2, and 24 rs 5. So the answer is 24.

Jan 26, 2011 | Computers & Internet

10x+25y

Jul 12, 2010 | Roomba Robotic Floor Bagless Vacuum

if you are looking for the answer, then here it is. Jenny gets 8 inches then Demi gets 4 inches then Drew gets 6 inches.

May 25, 2010 | Texas Instruments TI-30XA Calculator

press y= at the top of the calculator and use the variable button2nd row 2nd button.

Apr 13, 2010 | Texas Instruments TI-30XA Calculator

(13)3/8-(6)15/16

Jun 17, 2008 | Texas Instruments TI-84 Plus Silver...

Nov 22, 2013 | Bagatrix Algebra Solved! 2005 (105101) for...

Nov 22, 2013 | Bagatrix Algebra Solved! 2005 (105101) for...

155 people viewed this question

Usually answered in minutes!

×